2017
DOI: 10.1038/srep45260
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Amygdala Psychophysiological Connectivity Reveal Distinct Neural Networks for Facial Expressions of Basic Emotions

Abstract: The quest to characterize the neural signature distinctive of different basic emotions has recently come under renewed scrutiny. Here we investigated whether facial expressions of different basic emotions modulate the functional connectivity of the amygdala with the rest of the brain. To this end, we presented seventeen healthy participants (8 females) with facial expressions of anger, disgust, fear, happiness, sadness and emotional neutrality and analyzed amygdala’s psychophysiological interaction (PPI). In f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 117 publications
(168 reference statements)
4
79
1
1
Order By: Relevance
“…We agree with another study 38 , which found that changes in amygdala connections are usually compared across broad domains, such as emotion processing and attention. These results suggest that structure−function relationships between brain and emotion should be reconceptualized from a dynamic perspective.…”
Section: Discussionsupporting
confidence: 93%
“…We agree with another study 38 , which found that changes in amygdala connections are usually compared across broad domains, such as emotion processing and attention. These results suggest that structure−function relationships between brain and emotion should be reconceptualized from a dynamic perspective.…”
Section: Discussionsupporting
confidence: 93%
“…For example, deep brain stimulation of the basal ganglia causes impairment of emotion perception from facial and vocal expressions (Péron et al, 2010). More recent approaches have used connectivity-based measures to examine how these networks of brain regions coordinate their activity dynamically during emotion processing (Diano et al, 2017;Sato et al, 2017) . Extensive previous research has also examined how these intra-individual neural networks become disrupted during atypical development (Goulden et al, 2012;Lu et al, 2012;Nicholson et al, 2017).…”
Section: Intra-individual Neural Network For Emotional Processingmentioning
confidence: 99%
“…Fast emotional face processing with responses in the amygdala at 74 ms has been demonstrated in epilepsy patients being evaluated for temporal lobectomy; in nonhuman primates, pulvinar recordings show 50‐ms latency responses to face‐like stimuli, including cartoon faces . The traditional conception of the function of the amygdala as a “fear hub” (responsive to visual images of fear alone) has been challenged by recent fMRI studies, which have shown that the amygdala was comparably active in response to facial emotional expressions indicating anger, disgust, fear, happiness, and sadness …”
Section: The Psychiatry Of Cervical Dystonia and Disordered Social Comentioning
confidence: 99%